Impact of weather on the spring crops yield in Croatia with emphasis on climatic change and the 2014 growing season - Kovacevic, Vlado; Sostaric, Jasna (Acta Agraria Debreceniensis, 2016)
Main field crops in Croatia are maize, soybean, sunflower and sugar beet. By these crops are covered (status 2014) close to 50% (385 234 ha) of utilized arable land. Global warming, have often adverse influence on field crop yields. Aim of this study was testing precipitation and temperature regimes on spring crops yield in Croatia in 15-year period (1999–2013) and elaboration of the 2014 growing season with aspect of climatic change. Four growing seasons (2000, 2003, 2007 and 2012) were less favorable for maize because annual yield was bellow 5 t ha-1 (average 4.38 t ha-1), while in four more favorable years (2005, 2008, 2009 and 2010) annual yield was above 6.8 t ha-1 (average 7.32 t ha-1). Average precipitation and temperature for the April-September period in Osijek were 226 mm and 496 mm, 19.6 oC and 18.6 oC, for less and more favorable years, respectively. Yields of soybeans and sugar beet have mainly similar trend as maize yields in function of weather conditions, while sunflower is more susceptible to extremely moist growing seasons (for example, 2001 and 2005: 650 mm and 697 mm precipitation and very low yields in level 1.7 and 1.6 t ha-1, respectively). On the other side, under drought conditions of 2003, 2007 and 2012, yields of sunflower were above average in range from 2.5 to 2.7 t ha-1), while at same period yields of maize, soybean and sugar beet were drastically reduced. Average precipitation in the April-September period of 2014 for eight selected sites of Croatia was 756 mm or for 68% higher in comparison with the long-term average 1961–1990 with variation among the sites from 520 mm in Osijek to 910 mm in Varazdin. On the other side, average air-temperature in 2014 was 17.8 oC or for 0.7 oC higher with variations among the sites from 17.2 oC in Daruvar and Varazdin to 18.2 oC in Osijek and 18.3 oC in Gradiste. Under these favorable weather conditions, annual yields of maize (8.1 t ha-1), soybeans (2.8 t ha-1) , sunflower (2.9 t ha-1) and sugar beet 63.6 t ha-1) were considerable higher than usual.